(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Based on recent scenario, India has begun towards industrialization in all features of development. Construction industry in now days became a Fast, Developed, Modernized, Time Effective, Cost Efficient and Adopting Advance Construction Techniques. The Objective of study is to find the Present situation of the Pre-cast Construction Technique in India, Finding the Feasibility Study of Conventional (Cast In-situ) Vs. Pre-Cast Construction Method. This study focuses on different concepts of Pre-cast Construction Technique. A literature survey done highlights the facts associated with it. This study compares the parameters or area of effectiveness of both the Conventional and Pre-cast Technique.